Spatial design. Experiences and experiments of urban regeneration for a possible taxonomy - Carlo Martino; Meltem Eti Proto; Silvia Cosentino (Agathón)
The role played by the culture of Design in the context of the planning of public space has evolved over time. In the sphere of Architecture, the 1990s saw the opening of an international debate that encouraged a process of revising the training methods adopted until that time, in favour of new ones capable of placing people – the true users of objects, spaces, and architectures – at the centre. This raised the possibility of breaking down certain disciplinary boundaries in favour of a transdiscipline, the Design of Spaces and Architectures. Spatial Design calls back into question many of the assumptions of the Urban Planning and Architecture of the short century, starting precisely from the relationship between Space and the user. Through recent case studies, this essay proposes an embryonic taxonomy of public space, basing its perspective upon the scientific principle of the recurrence of certain design solutions.